Achieving inclusive agricultural growth - Birner, Regina; Mogues, Tewodaj; Akramov, Kamiljon T.; Cudjoe, Godsway; Asante, Felix Ankomah (International Food Policy Research Institute, 2007)
Agriculture is the backbone of Ghana’s economy, and this sector needs to play a key role if Ghana is to achieve the goal of becoming a middle income country by 2015. Despite its impressive progress in economic growth and poverty reduction, Ghana—like many other African countries—has had rather limited success in increasing smallholder agricultural production by enhancing productivity and competitiveness. Why? Like other countries, Ghana has to meet three challenges in selecting and implementing policies and programs for inclusive agricultural growth: the political feasibility challenge, the administrative feasibility challenge, and the fiscal feasibility challenge. This brief discusses options for overcoming these three challenges, and the role that current decentralization reforms can play in this regard.